Ontario ministry of the environment noise guidelines on wind power projects - Kowalewski, John (Canadian Acoustics, 2006)
In response to the anticipated introduction of large scale wind power projects for electricity generation in Ontario, the Ministry of the Environment (MOE) prepared specific guidelines for assisting proponents of such project to address the current environmental regulatory requirements. This article is a brief overview of the MOE review and approval process concerning environmental noise impacts of wind energy projects.